How important are hedge funds in a crisis? - Reint E. Gropp (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
Before the 2007-09 crisis, standard risk measurement methods substantially underestimated the threat to the financial system. One reason was that these methods didn't account for how closely commercial banks, investment banks, hedge funds, and insurance companies were linked. As financial conditions worsened in one type of institution, the effects spread to others. A new method that more accurately accounts for these spillover effects suggests that hedge funds may have been central in generating systemic risk during the crisis.
urn:nbn:de:hebis:30:3-336408
Keywords: 330; systemic risk analysis; statistical risk measurement; spillover effects